Description of the Services, Activities, and Interventions Within School-Based Physical Therapist Practices Across the United States. Issue 1 (17th October 2018) - Jeffries, Lynn M; McCoy, Sarah Westcott; Effgen, Susan K; Chiarello, Lisa A; Villasante Tezanos, Alejandro G
Abstract: Background: Students with disabilities receive school-based physical therapy services under the Individuals with Disabilities Education Improvement Act of 2004. Little research exists regarding therapy services in schools. Objective: This study explored the school-based services that students received and the activities and interventions that physical therapists implemented, and determined if services differed based on the student's functional gross motor ability and age. Design: This was a prospective observational cohort study using a practice-based evidence design. Methods: Data were collected by 109 physical therapists for 296 students, aged 5 to 12 years, receiving school-based physical therapy. Physical therapists completed the School-Physical Therapy Interventions for Pediatrics data form for 20 weeks during 1 school year. This evaluation included the type of service delivery, the amount of time spent on each student (consultation/documentation), minutes spent in activities, the specific interventions implemented, and the student's level of participation. The Gross Motor Function Classification System (GMFCS) was used to describe the students' functional ability. Results: Physical therapists provided an average of 26.7 min/wk (standard deviation [SD] = 15.1) of direct services and 13.1 min/wk (SD = 7.7) of services on behalf of the student. Primary activities were physical education/recreation (7.7 min/wk, SD = 8.2), mobility (6.7 min/wk, SD = 7.9), and sitting/standing/transitions (6.3 min/wk, SD = 8.1). Primary interventions were neuromuscular (32.5 counts per student, SD = 15.9), mobility (15.3 counts per student, SD = 14.65), and musculoskeletal (14.4 counts per student, SD = 10.3). Differences existed based on GMFCS but not student age. Limitations: Physical therapists reported School-Physical Therapy Interventions for Pediatrics data weekly, not necessarily after each therapy session. The GMFCS was used as a proxy of students' functional gross motor ability. Conclusions: Our description of services is provided to encourage physical therapists to reflect on the services they provide and to foster future examinations of service effectiveness.